Integrasi Pasar Beras di Tiga Negara Asean - Desi Aryani; Dedi Budiman Hakim; Ratna Winandi (Jurnal Ilmiah ESAI, 2010)
The initiation of market within ASEAN members especially for agricultural products will lead to the price relation on those products. The low of one price will take place if no trade barriers are imposed. As a result, price transmission and also market integration are hampered due to this trade policy. The objective of this study is to analyze spatial market integration of rice commodity in Thailand, Philippines, and the Indonesia. The studies used secondary data such as monthly price of rice and domestic exchange rate each country to US Dollar. Vector Auto Regression model was then applied to investigate whether rice markets in these countries are co-integrated. The result showed that rice market in Thailand, Philippines, and the Indonesia are co-integrated however at a weak level. This condition is a consequence of import policy (tariff and non-tariff) applied by these countries.Â Keywords: market integration, price, rice